Areawide pest management : theory and implementation (CABI, 2008)
This book aims (1) to lay out the historical underpinnings of the areawide pest (including weeds, plant and stored grain insect pests) management (AWPM) and to highlight current activity in the field; (2) to delve into concepts that have direct impact on the successful implementation of AWPM, which include: (i) biological and ecological concepts important for understanding the dynamics of populations in spatially heterogeneous environments; (ii) the critical role of inter-agency and multidisciplinary interactions in the development and implementation of AWPM programmes, which are often complex inter-agency and intergovernmental endeavours; (iii) the roles of modelling, meteorology and databases in AWPM programmes which, by their nature, are information intensive; and (iv) the importance of economic and sociological evaluation in successful AWPM implementation; and (3) to compile recent case examples of pest management programmes that have used the AWPM approach. A survey in presented on a wide variety of programmes developed for protecting agricultural and natural resource systems and which use a wide range of pest management tactics.